The Role of Acrolein in Neurodegenerative Diseases and Its Protective Strategy - Chang, Xinxin; Wang, Yudan; Zheng, Bing; Chen, Yi; Xie, Jianhua; Song, Yiming; Ding, Xiaomeng; Hu, Xiaoyi; Hu, Xiaobo; Yu, Qiang (Foods, 2022)
Neurodegenerative diseases are characterized by a massive loss of specific neurons, which can be fatal. Acrolein, an omnipresent environmental pollutant, is classified as a priority control contaminant by the EPA. Evidence suggests that acrolein is a highly active unsaturated aldehyde related to many nervous system diseases. Therefore, numerous studies have been conducted to identify the function of acrolein in neurodegenerative diseases, such as ischemic stroke, AD, PD, and MS, and its exact regulatory mechanism. Acrolein is involved in neurodegenerative diseases mainly by elevating oxidative stress, polyamine metabolism, neuronal damage, and plasma ACR-PC levels, and decreasing urinary 3-HPMA and plasma GSH levels. At present, the protective mechanism of acrolein mainly focused on the use of antioxidant compounds. This review aimed to clarify the role of acrolein in the pathogenesis of four neurodegenerative diseases (ischemic stroke, AD, PD and MS), as well as protection strategies, and to propose future trends in the inhibition of acrolein toxicity through optimization of food thermal processing and exploration of natural products.